Effectiveness of Jigsaw Cooperative Learning Models In Lessons of the Basics of Building Construction on Students Learning 'Outcomes Viewed From Critical Thinking Skills - Subiyantari, Ansheila Rusyda; Muslim, Supari; Rahmadyanti, Erina (Universitas Malikussaleh, 2019)
This study aims to analyze the differences in the effectiveness of the Jigsaw cooperative learning model and the direct learning model of student learning outcomes in DKB subjects in class X DPIB of Vocational High School 2 Surakarta; to analyze the differences in learning outcomes between students who have high critical thinking skills and students who have low critical thinking skills in DKB subjects in class X DPIB Vocational High School 2 Surakarta; and to analyze whether there is an interaction between the learning model and students' critical thinking skills towards student learning outcomes in the class X DKB DPIB Vocational High School 2 Surakarta. This study is a quantitative experimental study with a 2x2 factorial design. The sample of this study was the tenth grade students of DPIB Vocational High School 2 Surakarta in the 2018/2019 academic year, totaling 64 students. Data obtained from the results of observations, interviews, and tests. The data analysis technique uses 2-way Anava technique. The results is study's learning using Jigsaw cooperative learning model obtain the results of cognitive learning higher significant than learning outcomes cognitive students learn by using direct learning model on the subjects of DKB in Vocational High School 2 Surakarta; cognitive learning outcomes for students who have critical thinking skills height significantly higher than the results of cognitive learning students who have the skills to think critically low on the subjects of DKB in Vocational High School 2 Surakarta; and there is a very significant interaction between the learning model and the skill level which is critical to the cognitive learning outcomes of students in the DKB subjects at Vocational High School 2 Surakarta.